The acceleration of circular economy-based waste management through strengthening BUMDes Amarta as a response to the waste emergency in Yogyakarta - Lilia Pasca Riani; Endang Mulyani; Yuni Mariani Manik (Community Empowerment, 2026)
This community service program was conducted to strengthen the capacity of BUMDes Amarta in circular economy-based waste management to support village economic development. The program was designed through a series of training and mentoring activities focused on improving production capacity, business management, and marketing of recycled products. The activities also involved productive community groups around BUMDes Amarta so that waste management would not only address environmental issues but also generate economic value. The results showed that BUMDes Amarta managers were able to improve business management, optimize production processes, and enhance product quality. In addition, the target community groups experienced strengthened entrepreneurial skills, increased awareness of the importance of sustainable waste management, and improved ability to market products through various channels, including digital media. Overall, this program contributed to strengthening the capacity of BUMDes Amarta and its business partners, improving business competitiveness, and reinforcing the foundation for sustainable village economic development.